Deposition of Gold Nanoparticles via Galvanic Replacement in DMSO and Their Influence on Formation of Silicon Nanostructures - Mariana Shepida; Orest Kuntyi; Stepan Nichkalo; Galyna Zozulya; Sergiy Korniy (Advances in Materials Science and Engineering)
The process of gold nanoparticle (AuNP) precipitation on the silicon (Si) surface by galvanic replacement (GR) in dimethyl sulfoxide (DMSO) solution depending on the concentration of H[AuCl4], temperature, and duration was investigated. It is established that with an increase in the concentration of [AuCl4]− ions (from 2 to 8 mM H[AuCl4]), both the size of AuNPs and their surface coverage density are increased. It is demonstrated that an increase in temperature causes the size of AuNPs to increase from 40 to 80 nm at 40°C to 80–120 and 120–160 nm at 50 and 60°C, respectively. As the duration of the GR process increases, there is a tendency of the particle size growth. Under the studied deposition conditions, the organic aprotic solvent medium contributes to the formation of spherical AuNPs with 2D substrate filling. It is established that the AuNPs deposited on the silicon surface catalyze the process of metal-assisted chemical etching (MacEtch), which makes it possible to obtain Si nanostructures in the form of nanowire arrays.